245 Greenhouse Gas Emissions Mitigation Strategies. (8th October 2021) - Kebreab, Ermias; Honan, Mallory; Roque, Breanna; Tricarico, Juan
Abstract: Livestock production contributed 3.9% to the total greenhouse gas (GHG) emission from the US in 2018. Most studies to mitigate GHG from livestock are focused on enteric methane because it contributes about 70% of all livestock GHG emissions. Mitigation options can be broadly categorized into dietary and rumen manipulation. Enteric methane emissions are strongly correlated to dry matter intake and somewhat sensitive to diet composition. Dietary manipulation methods include increasing feed digestibility, such as concentrate to forage ratio, or increasing fats and oils, which are associated with lower methane emissions. These reduce digestible fiber that are positively related to methane production and more energy passing the rumen without being degraded, respectively. Rumen manipulation through feed additives can be further classified based on the mode of action: 1. rumen environment modifiers indirectly affecting emissions and 2. direct methanogenesis inhibitors. The rumen environment modifiers act on the conditions that promote methanogenesis. These include ionophores, plant bioactive compounds such as essential oils and tannins, and nitrate rich feeds that serve as alternative hydrogen sinks and directly compete with methanogens thereby reducing methane emissions. The inhibitor category include 3-nitroxypropanol and seaweeds containing halogenated compounds. The former was reported to reduce enteric methane emissions (g/d) by 39% in dairy and 22% in beef cattle. Seaweed, in particular Asparagopsis spp., reduced emissions intensity (g/kg milk) by up to 67% in dairy and emissions yield (g/kg dry matter intake) by up to 98% in beef cattle. Because inhibitors are structural analogs of methane, their mode of action is through competitive inhibition of the methyl transfer reaction catalyzed by methyl coenzyme-M reductase, the last enzyme in methanogenesis. The combination of dietary and rumen manipulation options, including feed additives, is expected to reduce enteric methane emissions by over 30% in the next decade without compromising animal productivity and health.